Informiranost mater o naravni in umetni prehrani ter delovanje La Leche League International - Pajnič, Manca (Obzornik zdravstvene nege, 2000)
The article presents the research work carried out in 1998 and covering 30 randomly selected mothers which children between six and 12 months of age. The aims were to find out about the awareness of mothers about the knowledge of mothers about natural and substitute feeding, and to find out whether the producers of artificial food propagate their products through health system. The article presents the world greatest non-governemental organization La Leche League International which has been endevoring for 30 years for greater promotion and advancement of breast feeding.
Keywords: dojenčki; dojenje; food; prehrana; umetna prehrana; zdravstvena vzgoja